2020
DOI: 10.1177/0022034520920593
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Bone Segmentation in Intraoral Ultrasonographs with Machine Learning

Abstract: The use of intraoral ultrasound imaging has received great attention recently due to the benefits of being a portable and low-cost imaging solution for initial and continuing care that is noninvasive and free of ionizing radiation. Alveolar bone is an important structure in the periodontal apparatus to support the tooth. Accurate assessment of alveolar bone level is essential for periodontal diagnosis. However, interpretation of alveolar bone structure in ultrasound images is a challenge for clinicians. This w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 37 publications
0
46
0
Order By: Relevance
“…Deep convolutional neural networks (CNNs) have recently become increasingly utilized in medical image segmentation (Litjens et al 2017; Altaf et al 2019) and have achieved state-of-the-art performances (Minnema et al 2018; Casalegno et al 2019; Nguyen et al 2020). The success of CNNs can be mainly attributed to their ability of learning nonlinear spatial features in input images.…”
Section: Introductionmentioning
confidence: 99%
“…Deep convolutional neural networks (CNNs) have recently become increasingly utilized in medical image segmentation (Litjens et al 2017; Altaf et al 2019) and have achieved state-of-the-art performances (Minnema et al 2018; Casalegno et al 2019; Nguyen et al 2020). The success of CNNs can be mainly attributed to their ability of learning nonlinear spatial features in input images.…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al [24] traced the contour in the US tongue image sequence using the active contour method with an automatic re-initialization technique. Chifor et al [25] explored the usage of US in the detection of gingival sulcus with the assistance of active contour based semiautomatic sulcus segmentation in the swine specimen; Nguyen et al [26] segmented alveolar bone in US images using the graph-cut based method with mandibular incisors from piglets, and subsequently adopted a deep learning approach to detect alveolar bone in humans [4].…”
Section: Discussionmentioning
confidence: 99%
“…Noninvasive techniques to image gingival soft tissues are not currently available in dentistry. Bi-dimensional ultrasound (2D US) imaging has already shown great potential for evaluating periodontal soft-tissue structures [2][3][4][5]. Lin et al demonstrated that periodontal probing depths could be measured with photoacoustic imaging [6].…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound scanning was performed at 20 MHz using a SonixTablet portable medical ultrasonic system (Analogic, Vancouver, BC, Canada) and a linear phased array transducer (L40-8/12, Analogic, Vancouver, Canada). The long axis of the transducer was positioned on a piece of 5 mm-thick gelatin-based gel pad located on the labial side of the tooth and gingiva in alignment with the longitudinal axis of the tooth [21]. The gel pad also functioned to ensure the region of interest (ROI) within the focal zone of the ultrasound beam for optimum resolution.…”
Section: Data Collectionmentioning
confidence: 99%
“…The applications and development of ultrasound in dentistry, especially in periodontics, have been extensively reported [14][15][16][17][18][19][20][21][22][23]. Ultrasound is a noninvasive, ionizingradiation-free, economical, and portable diagnostic tool for hard and soft tissue imaging.…”
Section: Introductionmentioning
confidence: 99%